Estimación de parámetros genéticos para edad al primer parto e intervalo entre partos en poblaciones bovinas de la raza Blanco Orejinegro (BON) en Colombia (2012)
ABSTRACT: to estimate genetic parameters for age at first calving (AFC) and calving interval (CI) in 22 herds of Blanco Orejinegro cattle in Colombia. Methods: a total of 1,256 records for AFC and 3,803 for CI, obtained between years 1981 and 2010 were analyzed. The (Co) variances components were estimated by a derivative-free restricted maximum likelihood procedure in a bi-trait animal model. Results: average of AFC and CI were 1,104 ± 141 and 487 ± 147 days, respectively. Heritabilities were 0.15 and 0.13 for AFC and CI, respectively, with -0.43 genetic correlation. The herd and year of birth were included as fixed effects for the AFC, while parity number and the covariate age of dam at farrow were analyzed for CI. All the effects had a significant influence over the CI variance. Conclusions: the values obtained for these traits indicate that selection for calving interval and age at first calving may have a relatively low impact, due to the large environmental effect on the variation of both parameters in these breed populations.